(untitled) (Nonconventional Technologies Review, 2023)
The Nonconventional Technologies Review is a scientific engineering journal published by Editura Politehnica din Timișoara on behalf of the Romanian Association for Nonconventional Technologies, which has started in 1997, with trimestrial appearance. The publication is addressed to all engineers and scientists interested in Nonconventional Technologies. This review publishes original scientific papers about machining by means of nonconventional technologies, such as EDM (Electrical Discharge Machining), Ultrasonic, Chemical and Electro-Chemical Erosion, Rapid Prototyping, Selective Laser Sintering etc, preferably written in English. All manuscripts are peer reviewed. The journal does not charge the authors any fees.